Evaluation of Oritavancin Dosing Strategies against Vancomycin-Resistant Enterococcus faecium Isolates with or without Reduced Susceptibility to Daptomycin in an In Vitro Pharmacokinetic/Pharmacodynamic Model - Belley, Adam (Antimicrob Agents Chemother, 2017)
The clinical development of nonsusceptibility to the lipopeptide antibiotic daptomycin remains a serious concern during therapy for infections caused by vancomycin-resistant Enterococcus faecium (VREfm). The long-acting lipoglycopeptide oritavancin exhibits potent in vitro activity against VREfm, although its safety and efficacy for treating clinical VREfm infections have not been established. In this study, novel dosing regimens of daptomycin and oritavancin were assessed against both VREfm and daptomycin-nonsusceptible VREfm isolates in an in vitro pharmacokinetic/pharmacodynamic model.